1992
DOI: 10.1121/1.402450
|View full text |Cite
|
Sign up to set email alerts
|

Segmental durations in the vicinity of prosodic phrase boundaries

Abstract: Numerous studies have indicated that prosodic phrase boundaries may be marked by a variety of acoustic phenomena including segmental lengthening. It has not been established, however, whether this lengthening is restricted to the immediate vicinity of the boundary, or if it extends over some larger region. In this study, segmental lengthening in the vicinity of prosodic boundaries is examined and found to be restricted to the rhyme of the syllable preceding the boundary. By using a normalized measure of segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
456
1
15

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 754 publications
(498 citation statements)
references
References 15 publications
26
456
1
15
Order By: Relevance
“…We used sequence duration as an index of the presence and/or strength of a prosodic boundary, based on the well-established effect of prosodic boundaries on preboundary segment duration (e.g. Beckman & Edwards, 1990;Turk & Shattuck-Hufnagel, 2000;Wightman et al, 1992). However, this in itself does not demonstrate that sequence duration is the dimension over which the computations leading to differential lexical activation take place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used sequence duration as an index of the presence and/or strength of a prosodic boundary, based on the well-established effect of prosodic boundaries on preboundary segment duration (e.g. Beckman & Edwards, 1990;Turk & Shattuck-Hufnagel, 2000;Wightman et al, 1992). However, this in itself does not demonstrate that sequence duration is the dimension over which the computations leading to differential lexical activation take place.…”
Section: Discussionmentioning
confidence: 99%
“…Cooper & Paccia-Cooper, 1980; but see Pierrehumbert & Liberman, 1982;Shattuck-Hufnagel & Turk, 1996, and references therein, for discussions on the mapping between syntax and prosody). Ladd and Campbell (1991) and Wightman, Shattuck-Hufnagel, Ostendorf, and Price (1992), amongst others, have shown that the amount of preboundary lengthening varies with the level of the prosodic boundary. Segmental lengthening is stronger at the edge of high prosodic domains, such as intermediate and intonational phrases, than at the edge of lower prosodic domains, such as prosodic words and accentual phrases.…”
Section: Introductionmentioning
confidence: 99%
“…As preboundary lengthening has widely been considered as one of the primary phonetic correlates of prosodic structure (e.g., Wightman et al, 1992), we first examined whether our threeway prosodic grouping (based on pause and boundary tones; see Section 2.2) could be corroborated by differences among the three prosodic groups (BG, SM and WD) in the duration of the preboundary syllables. There was a significant Boundary effect on preboundary syllable (CV#) duration (F [1.4, 14.5] ¼ 90.42, po0:0001).…”
Section: Preboundary Lengtheningmentioning
confidence: 99%
“…Primarily, speakers mark boundaries with increased duration of pre-boundary words (Price, et al, 1991;Wightman, Shattuck-Hufnagel, Ostendorf, & Price, 1992;Ferreira, 1993;Lehiste, Olive & Streeter, 1976;Selkirk, 1984;Schafer, et al, 2000;Snedeker & Trueswell, 2003) and / or silence (Lehiste, 1973;Klatt, 1975;Cooper & Paccia-Copper, 1980). In addition, speakers often raise or lower their pitch at the end of intonational phrases (Streeter, 1978;Pierrehumbert, 1980).…”
mentioning
confidence: 99%